Transaneurysmal Repair of a Giant Calcified Submitral Left Ventricular Aneurysm - Sanagar,Sachin (2020)
Abstract Submitral left ventricular aneurysm is a rare cardiac pathology with very few cases reported in the literature. These are nonischemic aneurysms mostly reported from Africa. Patients with submitral aneurysm exhibit varied clinical manifestations. We report a case of calcified submitral aneurysm and its successful surgical management through a transaneurysmal approach.